2018
DOI: 10.1186/s12964-018-0220-7
|View full text |Cite
|
Sign up to set email alerts
|

A highlight on Sonic hedgehog pathway

Abstract: Hedgehog (Hh) signaling pathway plays an essential role during vertebrate embryonic development and tumorigenesis. It is already known that Sonic hedgehog (Shh) pathway is important for the evolution of radio and chemo-resistance of several types of tumors. Most of the brain tumors are resistant to chemotherapeutic drugs, consequently, they have a poor prognosis. So, a better knowledge of the Shh pathway opens an opportunity for targeted therapies against brain tumors considering a multi-factorial molecular ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
289
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 333 publications
(325 citation statements)
references
References 126 publications
2
289
0
2
Order By: Relevance
“…[162] Although most mutations are observed in the drug-binding pocket of SMO, mutations in genes related to ciliogenesis, including OFD1, IFT80, and retinitis pigmentosa GTPase regulator-interacting protein 1 (RPGRIP1), have also been identified. [160,161] Small molecules have been identified that inhibit GLI-A [162,[165][166][167][168][169][170][171] and reintroduce primary cilia. [160] Additional mutations, such as loss-of-function mutations in SUFU, increase the nuclear transport of GLI2 and enhance hedgehog signaling, resulting in the aggressive growth of medulloblastoma and BCC resistant to SMO inhibitors.…”
Section: Hedgehog Signaling Regulates Cancer Cell Proliferation Throumentioning
confidence: 99%
“…[162] Although most mutations are observed in the drug-binding pocket of SMO, mutations in genes related to ciliogenesis, including OFD1, IFT80, and retinitis pigmentosa GTPase regulator-interacting protein 1 (RPGRIP1), have also been identified. [160,161] Small molecules have been identified that inhibit GLI-A [162,[165][166][167][168][169][170][171] and reintroduce primary cilia. [160] Additional mutations, such as loss-of-function mutations in SUFU, increase the nuclear transport of GLI2 and enhance hedgehog signaling, resulting in the aggressive growth of medulloblastoma and BCC resistant to SMO inhibitors.…”
Section: Hedgehog Signaling Regulates Cancer Cell Proliferation Throumentioning
confidence: 99%
“…An another example of a protein with dual lipidation is sonic hedgehog (shh), which possesses a C16 palmitoyl group at the N‐terminus and cholesterol at the C‐terminus (Figure c) . An initial precursor of shh undergoes autoproteolysis and addition of a cholesterol moiety at the C‐terminus of shh ( C ‐cholesterylation).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that TMZ is inefficient in inducing GSC death [6,7]. Moreover, the tumor microenvironment (TME) recapitulates the activation of several pathways including Sonic hedgehog (SHH), Wingless (WNT), Notch and transforming growth beta (TGF-β) [8][9][10][11], responsible for GSCs' maintenance in the tumor mass [12,13]. In fact, the upregulation of the SHH pathway preserves the main characteristics of GSC such as the ability of self-renewal and chemoresistance in tumors [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the upregulation of the SHH pathway preserves the main characteristics of GSC such as the ability of self-renewal and chemoresistance in tumors [14,15]. In general, the SHH signaling pathway is activated when SHH binds to 12-transmembrane protein Patched (PTCH), named PTCH1 or PTCH2 and consequently occurs the releasing of 7-transmembrane protein Smoothened (SMO), which in turn can be activated and stabilized initiating the SHH downstream signaling cascade [11,[16][17][18]. This downstream cascade produces the translocation of GLI family proteins from the cytoplasm to the nucleus and consequently, it starts the transcription of target genes including PTCH, GLI, SOX-2, and OCT-4 [19,20].…”
Section: Introductionmentioning
confidence: 99%